Significant Trends Affecting Your Audiences - C. B. Ratchford (Journal of Applied Communications, 1970)
I suspect that AAACE members, like other professional groups, spend much of their time on improving skills and techniques and, as a result, tend to overlook some of the larger scale developments that are equally, if not more, important to their work.